Software Engineering: A Practitioner's Approach (Mcgraw-Hill Series in Computer Science) - Roger S. Pressman (MC Graw Hill, 2005)
For over 20 years, Software Engineering: A Practitioner's Approach has been the best selling guide to software engineering for students and industry professionals alike.